The Effect of Special Exercises According To Herman’s thinking Patterns On Learning Spiking In Volleyball For Second Year College of Physical Education and Sport Sciences’ Students - Kahlil, Reiad; Hikmat, Shams (Journal of Physical Education, 2018)
The Effect of Special Exercises According To Herman’s thinking Patterns On Learning Spiking In Volleyball For Second Year College of Physical Education and Sport Sciences’ Students The importance of the research lies in designing special exercises according to Herman’s thinking patterns for developing spiking in volleyball. The research aimed at identifying the effect of these exercises on learning spiking in volleyball. The problem of the research was in not paying attention to individual difference in teaching volleyball skills according to thinking patterns. The researchers hypothesized statistical differences between experimental and controlling groups in learning and retaining some artistic skills. They concluded that the program was effective in teaching spiking for the subjects understudy. In addition to that, the designed exercises were effective in learning spiking in the experimental group compared to the controlling group. Finally the researchers recommended using these exercises in learning spiking for sophomore students for learning and retaining spiking as well as benefiting from the current study in designing teaching programs according to thinking patterns.